2015
DOI: 10.1097/md.0000000000002196
|View full text |Cite
|
Sign up to set email alerts
|

Transitional Care and Adherence of Adolescents and Young Adults After Kidney Transplantation in Germany and Austria

Abstract: Transition from child to adult-oriented care is widely regarded a challenging period for young people with kidney transplants and is associated with a high risk of graft failure.We analyzed the existing transition structures in Germany and Austria using a questionnaire and retrospective data of 119 patients transferred in 2011 to 2012.Most centers (73%) confirmed agreements on the transition procedure. Patients’ age at transfer was subject to regulation in 73% (18 years). Median age at transition was 18.3 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 31 publications
1
35
0
1
Order By: Relevance
“…The sample size of this pilot study represents about 10% of children aged 6-18 with working kidney transplant in Germany [38,39]. In this matched cross-sectional study we found significant differences in micro-vascular parameters between patients treated with either an EVR-based regime or a standard immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 51%
“…The sample size of this pilot study represents about 10% of children aged 6-18 with working kidney transplant in Germany [38,39]. In this matched cross-sectional study we found significant differences in micro-vascular parameters between patients treated with either an EVR-based regime or a standard immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 51%
“…The use of transition of care facilities should be implemented to provide a smooth transition to self-care. Research in the young adults and adolescents population and the use of transition of care for kidney disease has become promising in recent years (4).…”
Section: Transition Of Care Centersmentioning
confidence: 99%
“…11 More effective educational programs, better engagement of younger recipients, and use of long-acting parenteral immunosuppressive therapies and once-daily drugs can be used to reduce the complexity of immunosuppressive regimens and improve adherence. 74,86,95,271 The long-term use of belatacept significantly reduces the risk of de novo DSAs compared with cyclosporine A-based immunosuppression. 271 However, it is still not fully clear whether the decreased incidence of de novo DSAs arises from better adherence, the drug's ability to block the second signal and T-cell follicular helper cells, or both factors.…”
Section: Highly Modifiable Contributors To Dsa Occurrencementioning
confidence: 99%